Defence of insanity & diminished responsibility in our system of criminal justice / Nor Zihan M. Zain - M. Zain, Nor Zihan (Faculty of Law, 1986)
The term "insanity" is, usually regarded by lawyers as a medical; term and by doctors as a legal term. In fact there is no legal or medical definition of insanity, but in medical parlance, it has a fairly clear and definite meaning, namely, that the patient is.suffering from a major mental disease (usually a psychosis). Over the years, judges and academic writers have assumed that when an accused person pleads the defence of insanity,he pleads what Glanville Williams has aptly described as "M'Naghten Madness".In 1843 M'Naghten, a Scotsman, who was suffering from a delusion that he was being persecuted killed Sir Robert Peel's secretary on the mistaken belief that the latter was Sir Robert. On a plea of insanity, M'Naghten was acquitted of the charge of murder and sent to a mental asylum